2022
DOI: 10.4103/jfmpc.jfmpc_1405_21
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal crisis in a patient with APS2 due to COVID-19

Abstract: COVID-19 (corona virus disease 2019), caused by the severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2), has spread throughout the globe and affected millions of people worldwide. Here, we report a patient with autoimmune polyglandular syndrome type 2 who presented with adrenal crisis, precipitated by COVID-19. We intend to highlight the importance of stress dosing in preventing adrenal crisis in patients with adrenal insufficiency (AI). A uniform structured education programme is needed to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“… 145 Moreover, an adult male with APS-2 developed an adrenal crisis while going through COVID-19 infection. 146 A 14-year-old girl previously known with vitiligo was confirmed with adrenal crisis due to COVID-19 infection; she developed multisystem inflammatory syndrome in children (MIS-C), this being the first pediatric case of autoimmune AI and hypothyroidism that were diagnosed due to the infection. 147 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 145 Moreover, an adult male with APS-2 developed an adrenal crisis while going through COVID-19 infection. 146 A 14-year-old girl previously known with vitiligo was confirmed with adrenal crisis due to COVID-19 infection; she developed multisystem inflammatory syndrome in children (MIS-C), this being the first pediatric case of autoimmune AI and hypothyroidism that were diagnosed due to the infection. 147 …”
Section: Discussionmentioning
confidence: 99%
“…145 Moreover, an adult male with APS-2 developed an adrenal crisis while going through COVID-19 infection. 146 A 14-year-old girl previously known with vitiligo was confirmed with adrenal crisis due to COVID-19 infection; she developed multisystem inflammatory syndrome in children (MIS-C), this being the first pediatric case of autoimmune AI and hypothyroidism that were diagnosed due to the infection. 147 Of note, a study analyzing medical deprivation rate in patients with endocrine disease during pandemic showed that individuals with AD had the lowest rate (of 0%) as opposed, for instance, with high rates for differentiated thyroid carcinoma (of 89%).…”
Section: Covid-19 Infection and Addison's Diseasementioning
confidence: 99%
“…In that case, an adolescent patient developed primary adrenal insufficiency and autoimmune hypothyroidism just weeks after presumed COVID-19 infection [ 10 ]. There also is a case report of adrenal crisis in APS-2 patients due to COVID [ 18 ], but other studies examining the occurrence of APS-2 with COVID-19 are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy as to whether patients with primary or secondary adrenal insufficiency, including OIAI, have an elevated risk of contracting COVID-19 and face a greater risk of a complicated course, because the infection may trigger a possibly lifethreatening adrenal crisis [38][39][40][41]. In cases of a patient with both COVID-19 and OIAI, an increased dose of glucocorticoid replacement therapy is recommended [38].…”
Section: Adrenal Insufficiency In the Covid Eramentioning
confidence: 99%